Risk sharing revisited: Empirics and concepts - Patrick Christian Harms (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2021)
The paper adds to the literature as follows: starting from the benchmark model of Asdrubali et al. (1996), we reproduce the original specification with a data set obtained from the authors as well as possible. In a second step, this specification is brought to euro area data. Again, the results are broadly in line with the existing literature (Furceri and Zdzienicka, 2015). We report rolling window and recursive estimates and show high time variation in the coefficients. The parameter estimates are related to a recession dummy in the euro area (confirmed by structural break tests) and very sensitive to the exclusion of countries like Ireland and Luxembourg. Granger causality analysis in a VAR approach also points to a strong dependence on the macroeconomic environment. Last but not least we discuss shortcomings of the approach. All in all the high time variability of the results in a benchmark model in the spirit of Asdrubali et al. (1996) makes it difficult to draw robust policy recommendations for the euro area.
Keywords: F41; F32; F36; 330; Economic and Monetary Union; Risk Sharing Mechanisms